Analisis dan Penerapan VPN Site to Site Jaringan Antargedung Universitas Bina Darma - Nabil, Muhammad Faiz; Mukti, Aan Restu; Suryayusra, Suryayusra; Irawan, Dedi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This research analyzes the implementation of a site-to-site Virtual Private Network (VPN) between buildings at Universitas Bina Darma using two protocols: Point-to-Point Tunneling Protocol (PPTP) and Layer 2 Tunneling Protocol (L2TP). The objective is to evaluate network performance based on Quality of Service (QoS) parameters, including delay, throughput, packet loss, and jitter. The study employs an experimental method by configuring VPN connections on MikroTik devices installed in each building and conducting tests using the iperf3 application. The results show that L2TP provides a lower average delay (6 ms) compared to PPTP (18 ms) and achieves higher throughput, reaching 95.8 Mbps at 100 Mbps bandwidth. In contrast, PPTP records lower throughput, with an average of 71.9 Mbps and TCP throughput of only 3.8 Mbps, but demonstrates better stability in terms of packet loss (0–0.0046%) and jitter (0.8–1.4 ms). In conclusion, PPTP is more suitable for stable data transmission, while L2TP is preferable for high-speed communication, and the choice of protocol should be adjusted to specific network requirements.